The attachment among generation in pertuating the female genital mutilation in Lombok - Puspita Dewi; Liana Mustaip; Riyana Rizki Yuliatin (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2022)
FGM is maintained by local people in Lombok from generation to other generations. This study aims to explore how FGM practice still exists in Lombok. The qualitative research was used to discover the point of view of the subjects. The data was analyzed by content analysis. The data were gained from Focus Group Discussion (FGD) and in-depth interviews in three generations: Baby Boomer, Gen X, and Gen Y (Millennial). The research results show that the FGM perpetuates continuously because the attachment among generations. The attachment as one of the factors in pertuating the FGM because of the obedience among generations. Moreover, the religious aspect has a pivotal role in performing the FGM. The practice perpetuates the symbolic violence to the women. As result, both factors lead society’s perspective to consider that FGM as a collective responsibility. This study is suggested for policy-maker.